“Oh de casa! oh de fora! vamos chegando e vamos entrando” : lavradores ás margens do Araguaia mato-grossense (1950 - 1990) - Cantuário, Maria Raimunda dos Santos (2012)
This work is an ethnographic inventory on some aspects of the lifestyle of a group of descendants of northeastern farmers who settled the left bank of the Araguaia River, on land now belonging to the municipality of Sao Felix do Araguaia / MT. In the period that corresponds to the decades from 1950 to 1990, that definition refers to the period in which they settled in the study area and subsequently migrated from this area. The issues discussed were the relationship of these farmers with the land and the water and the bonds of sociability among tissues from the production practices of the flour and the weaving of the network.